2004
DOI: 10.1002/pssb.200304571
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal degradation of 2.25Cr–1Mo steel by magnetic Barkhausen noise

Abstract: An attempt was made to evaluate nondestructively thermally degraded 2.25Cr -1Mo steel by magnetic Barkhausen noise (MBN) technique. Microstructural analysis (mean size of carbides), measurement of mechanical property (hardness) and magnetic Barkhausen noise parameters (rms voltage, count) for a wide range of specimens isothermally degraded at 630 °C were carried out to obtain the correlations between them. Both the rms voltage (MBNrms) and the count (MBNcount) of MBN signal were observed to increase rapidly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In particular, large values of RCP are obtained to be 108.9, 106.1, 98.6, and 106.8 J/kg at a relative low field change of 2 T for the Li-, free-, Na-, and K-doped samples, respectively. The obtained RCP values are about 60% of pure Gd metal with a same field change of 2 T [28]. Although the values of RCP for present samples are smaller than that of conventional magnetic refrigerant materials, perovskite manganites are inexpensive, good chemical stability, easier to fabricate, and tunable T C by element doping, and therefore could be promising candidates for magnetic refrigeration.…”
Section: Resultsmentioning
confidence: 74%
“…In particular, large values of RCP are obtained to be 108.9, 106.1, 98.6, and 106.8 J/kg at a relative low field change of 2 T for the Li-, free-, Na-, and K-doped samples, respectively. The obtained RCP values are about 60% of pure Gd metal with a same field change of 2 T [28]. Although the values of RCP for present samples are smaller than that of conventional magnetic refrigerant materials, perovskite manganites are inexpensive, good chemical stability, easier to fabricate, and tunable T C by element doping, and therefore could be promising candidates for magnetic refrigeration.…”
Section: Resultsmentioning
confidence: 74%
“…Also, Yoshino et al 14 reported that in steels containing only ferrite, the coercive force was inversely proportional to the grain size. Byeon et al 15 experimentally studied the thermal degradation of bainitic 2.25Cr–1Mo steel using the magnetic Barkhausen noise technique. Jiles 16 investigated the effect of plastic compressive deformation on high Cr steel under three sets of microstructural conditions: ferrite/pearlite, ferrite/bainite, and tempered martensite.…”
Section: Introductionmentioning
confidence: 99%
“…Establishment of robust assessment techniques to detect a sub-critical, yet significant damage prior to a crack initiation can substantially enhance the reliability and maintainability of power plant components such as pressure vessel and boiler tube [1]. Several nondestructive evaluation techniques, mostly reflect averaged microstructural changes in the specimen, have been applied to assess carbide-induced thermal degradation, including: replication [2], ultrasonic [3], Barkhausen noise [4]. Based on the nondestructively replicated image, mean size of grain and/or carbide was correlated with remaining life time of components [2].…”
Section: Introductionmentioning
confidence: 99%